2020
DOI: 10.1038/s41598-020-76987-2
|View full text |Cite
|
Sign up to set email alerts
|

The long-lasting post-stimulation inhibitory effects of bladder activity induced by posterior tibial nerve stimulation in unanesthetized rats

Abstract: Tibial nerve stimulation (TNS) is one of the neuromodulation methods used to treat an overactive bladder (OAB). However, the treatment mechanism is not accurately understood owing to significant differences in the results obtained from animal and clinical studies. Thus, this study was aimed to confirm the response of bladder activity to the different stimulation frequencies and to observe the duration of prolonged post-stimulation inhibitory effects following TNS. This study used unanesthetized rats to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…However, the therapy appears to modify spinal cord reflexes and brain involvement via afferent signals rather than direct motor stimulation of the detrusor or urethral sphincter. According to the most widely recognized explanation, neuromodulations interrupt or interfere with the afferent nerve input to the sacral spinal cord, limiting detrusor overactivity and resulting in clinical alleviation of urine frequency and urgency [ 31 , 32 ]. Electrical stimulation of the pelvic nerve, pudendal nerve sensory fibers, or muscular nerve fibers from lower limbs like the posterior tibial nerve can inhibit spinal micturition centers [ 33 , 34 ].…”
Section: Micturition Reflex and Neuromodulation Mechanismmentioning
confidence: 99%
“…However, the therapy appears to modify spinal cord reflexes and brain involvement via afferent signals rather than direct motor stimulation of the detrusor or urethral sphincter. According to the most widely recognized explanation, neuromodulations interrupt or interfere with the afferent nerve input to the sacral spinal cord, limiting detrusor overactivity and resulting in clinical alleviation of urine frequency and urgency [ 31 , 32 ]. Electrical stimulation of the pelvic nerve, pudendal nerve sensory fibers, or muscular nerve fibers from lower limbs like the posterior tibial nerve can inhibit spinal micturition centers [ 33 , 34 ].…”
Section: Micturition Reflex and Neuromodulation Mechanismmentioning
confidence: 99%
“…This possibility is well in line with the current literature in animal research, which shows different outcomes based on a variety of stimulation parameters, including frequency. 36 …”
Section: Discussionmentioning
confidence: 99%
“…23 Therefore, the accuracy of most existing studies is limited because of the use of anesthetized animals for micturition reflex evaluation. 17 Although Park et al 13 have reported a poststimulation inhibitory effect of TNS for an average of ten hours in unanesthetized active rats by using an implantable electrical stimulator and a wireless power delivery system, it is difficult to rule out interference from other stimuli in conscious animals, such as body movement, pain, and fear, resulting in significant between-subject discrepancy and inaccurate results. In this context, the decorticated rat model can overcome these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is difficult to keep the stimulator still for a long time in an unanesthetized, vigorous animal for outside bladder stimulation and the body movement of experimental animals may affect the results, leading to a significant between-subject discrepancy. In the study by Park et al, 13 the poststimulation inhibitory effect showed a large discrepancy in inhibitory duration for each animal (3-25 hours). Therefore, further studies with a more reliable animal model are needed to determine the prolonged poststimulation inhibitory effect of TNS.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation